Forest restoration, resources sustainable use and high-quality sustainable management - Zhongsheng Guo (Global Journal of Ecology - Peertechz Publications, 2023)
As the economy develops and the population increases, there is an increasing demand for goods such as timber, food, medicine, and so on, and ecological services such as fresh water and the environment. Because goods and services produced by the original forest cannot meet the increasing need of people, so most of the original forest has become farmland, plantation, and grass. In the process of Forest restoration, a lot of exotic plants was introduced to produce special products and service. As exotic plants grow, vegetation declines, and crop failure will happen in dry years or resource waste in wet years. In order to solve these problems, Years of theoretical research and investigation in fixed positions have shown that there is a soil water resources use limit by plants and the soil water vegetation carrying capacity in the process of vegetation restoration. When the soil water resources in the range of the maximum infiltration depth are equal to the soil water resources use limit by plants, the plant water relation enters the key period of plant water relation regulation. If existing plant density is more than the soil water vegetation carrying capacity in the key period of plant water relation regulation, the plant water relation has to be regulated on the soil water vegetation carrying capacity to get maximal yield and service and realize high-quality sustainable management of forest vegetation in a water shortage area.